Administrative Barriers to the Implementation of Inclusive Education - Berwal, Sandeep; Bala, Renu; Punia, Poonam (JOURNAL OF INDIAN EDUCATION, 2020)
This study was undertaken to identify certain administrative barriers that impede the implementation of inclusive education in primary schools of Haryana. The sample comprised 28 school heads selected from nine educational blocks of four districts through a multistage random sampling technique. An ‘Administrative Barriers Checklist,’ covering six broad areas of ‘school working’ and 25 standards on the ‘functions of school head’, given in the framework of Sarva Shiksha Abhiyan (SSA), was used to determine if any standard listed in the checklist was a barrier to inclusion. Each school head was contacted personally while filling up the checklist. The results show that only six standards out of 25 were met fully by head teachers whereas 19 unmet standards were counted as administrative barriers to the implementation of inclusive education. This would imply that school heads being local administrators have failed to comply with the standards given in Sarva Shiksha Abhiyan (SSA) framework for implementing inclusive education. In particular, the heads failed in their function to encourage the teachers to use technology in the classroom, prepare and use the Individual Educational Plan (IEP), etc. The study recommends the government to undertake intensive in-service orientation and training programmes for the school heads to understand and implement inclusive education strictly as per the guidelines of Sarva Shiksha Abhiyan (SSA). The study has its implications for policymakers, teachers, media personnel, children with disabilities, and their parents.